Finding character strengths through loss: an extension of Peterson and Seligman (2003) - Schueller, Stephen M.; Jayawickreme, Eranda; Blackie, Laura E.R.; Forgeard, Marie, J.C.; Roepke, Ann Marie (Taylor & Francis, 2014)
People can experience positive changes even in the midst of adversity and loss. We investigated character strengths following three recent shooting tragedies. Using an Internet database of respondents to the Values in Action Inventory of Strengths (VIA-IS), we compared responses from three groups of participants (N = 31,429) within close proximity of each event: those who completed it eight months prior to the event, and one month and two months after. Results suggested that for one of the events, participants who completed the VIA-IS after the event showed slightly different levels of self-reported character strengths compared to participants who completed the VIA-IS before the event, with some mean levels higher and others lower. The observed differences in character strengths were inconsistent across follow-up periods, and effect sizes were small (d values from –0.13 to 0.15). These findings raise questions about whether and how tragedies might catalyze differences in character strengths.